Analisis Harga Dan Saluran Distribusi Guna Meningkatan Volume Penjualan - Ismiati Ismiati; Tanto Askriyandoko Putro (RISK : Jurnal Riset Bisnis dan Ekonomi, 2022)
Competition in the business world demands that every company gain market share by increasing its sales volume accompanied by marketing strategies, namely price and distribution channels. Where the price is a monetary unit while the distribution channel is an intermediary from producers to consumers. The purpose of this study was to analyze prices and distribution channels on sales volume at the Putri kuning home industry, using quantitative methods. The sampling technique uses employee and customer respondent data. Based on the results of the calculation of the price variable, it can be seen a significant value of 0.025. So it can be concluded that the price has no significant effect on sales volume where Ho is accepted and Ha is rejected because the significant value of the price variable is greater than 0.05. Based on the results of the calculation of the distribution channel variable, it can be seen a significant value of 0.202. So it can be concluded that the distribution channel has no significant effect on sales volume where Ho is accepted and Ha is rejected because the significant value of the distribution channel variable is greater than 0.05. This shows that if the use of distribution channels is not effective and efficient, it will have an impact on sales volume.